PENGEMBANGAN MODEL PREFERENSI PERILAKU PEMILIHAN RUTE TRANSPORTASI DARAT DENGAN ANALISIS CONJOINT DI KOTA SEMARANG - Siswanto, Joko; Riyanto, Bambang (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The concept of behavioral preferences of consumers in the selection of the transport route is not separated from the analysis to determine the factors to be considered as a preference in choosing the right route and meet consumer desires. The concept of utility road as an assessment of consumer preferences as the traveler can be used as another parameter that can be used as a complement to these elections besides the physical parameters of road network Many aspects of a utility that allows a determinant of consumer preference studies using the concept of choice in getting multiatribut preference models. Multiatribut analysis in general is an analysis of the use of mostly attributes and by using statistical analysis will result in a more compact model Research results Preferences Behavioral Model Development Land Transport Route Selection in Semarang Indonesia can be done by using Conjoint analysis multiatribut . Preference route choice behavior in Semarang Indonesia is directly proportional to the convenience factor , the crowd , the facilities , convenience , safety and inversely proportional to the density . Attributes are considered the most important is the ease of attributes , whereas attributes are considered insignificant relative comfort attributes